Skena Musik Independen Indonesia Analisis Wacana Kritis Van Dijk Pada Komentar Video Clip Lagu “Runtuh” – Feby Putri Ft Fiersa Besari - Adine Venita Rizki; Nabila Sahda Brahmasta; Ryan Fergiansyah; A.A.I. Prihandari Satvikadewi (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
This research analyzes the song "Runtuh" popularized by two well-known indie musicians in Indonesia, Feby Putri and Fiersa Besari. The method used to analyze this song is using the Critical Discourse Analysis method which is used as a method to explore how the trend of independent music is being loved by independent music lovers, especially teenagers who have a connection to this song so that the song "Runtuh" has a very meaningful meaning and is able to understand the situation experienced by listeners, especially teenagers. Based on the comments on the music streaming platform, it shows that this song is not only a reflection of the songwriter's personal experience, but can represent the younger generation, especially teenagers who often feel marginalized by a situation. Furthermore, this research is expected to contribute to the role of the independent music scene in Indonesia in shaping identity among young people or teenagers.